In Search of Peaceful Future of the Asia-Pacific Maritime World: Formulating the Role of Indonesian Navy - Amarulla Octavian (Diponegoro University, 2017)
This article discusses how to formulate the role of Indonesian Navy as an effort to make peaceful future in the Asia-Pacific maritime world through military history perspective. Pacific War in World War II is perfect examples of how history could not be separated from the development of any nation in the world. No country could establish itself as a developed state without developing an internal awareness of its history. It is a record of the nation, either positive or negative, of one generation to be learned by the next one. Although our very existence is a result of the history of the past, the path of our future lies in our hands. It is important for Indonesia’s current generation to excel positive contribution to the nation. This country is currently facing complex challenges, and the policy and strategy we will take would determine the face of our history in the future. Any mistakes in the formulation of policy and strategy would eventually have negative implication to our country; influencing our future.